Developing Culturally and Developmentally Appropriate Early STEM Learning Experiences. Issue 1 (2nd January 2021) - Li, Hui; Forbes, Anne; Yang, Weipeng
ABSTRACT: This special issue on early STEM education collects ten articles that present a series of studies covering topics about curriculum and pedagogy, teacher education and professional development, family environment, and inclusive education for enhancing young children's STEM learning experiences. These collected studies have presented empirical evidence obtained from diverse cultural contexts, including Australia, Germany, Hong Kong, Mainland China, Singapore, and the United States. With varying designs and diversified approaches, these studies jointly present a vivid picture of the STEM world and may therefore provide some contributions to theoretical developments and practical improvements.